2011
DOI: 10.1111/j.1464-410x.2011.10279.x
|View full text |Cite
|
Sign up to set email alerts
|

Intratesticular pressure after testicular torsion as a predictor of subsequent spermatogenesis: a rat model

Abstract: What’s known on the subject? and What does the study add? Testicular torsion results in atrophy rates of more than 25% despite prompt surgical management, and there is no reliable intraoperative critieria to judge the viability of the testis, except the testicular appearance after scrotal incision. We demonstrated that less reduction of ITP after detorsion correlated with worse subsequent spermatogenesis. This result suggests that ITP can be the index to determine removal of the affected testis during surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…17 Mean pre-torsion intratesticular pressure (5.9 cm H 2 O), 2-hour torsion pressure (19.7) and detorsed intratesticular pressure (8.2) were identified. A negative correlation between the differential ICPs (torsion ICP/detorsion ICP) and histological damage markers were observed and found statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…17 Mean pre-torsion intratesticular pressure (5.9 cm H 2 O), 2-hour torsion pressure (19.7) and detorsed intratesticular pressure (8.2) were identified. A negative correlation between the differential ICPs (torsion ICP/detorsion ICP) and histological damage markers were observed and found statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…They showed in rats that smaller reductions in the intratesticular pressure following an episode of detorsion were more likely to result in disturbances of spermatogenesis. [39] These results are quite promising and should encourage a multi-institutional study to evaluate the efficacy of this surgical technique.…”
Section: Novel Surgical Techniquesmentioning
confidence: 97%
“…11 Moritoki et al demonstrated, using an animal model, increased intra-testicular pressures during torsion, as well as a positive correlation between the degree of pressure reduction post-detorsioning and later organ functionality. 12 This indicates compartment syndrome may well play a significant part in the pathophysiological process, and highlights the clinical question as to whether tunica albugenia fasciotomy has a role in surgical management. This was recognised by Figueroa et al, who preliminarily recommended its use following 11 documented fasciotomies, albeit acknowledging their limited sample size, in the management of clinically marginal torsed testes following detorsion.…”
Section: Pathophysiology and Compartment Syndromementioning
confidence: 99%